Ultrasound of the Postoperative Hip - Craig, Joseph G. (Seminars in Musculoskeletal Radiology, 2013)
Imaging of the postoperative hip with ultrasound can be difficult and challenging. The primary role of ultrasound is to help determine whether or not there is infection. It is difficult at times to differentiate between complex fluid and synovium. Whether fluid is infected or not cannot be determined by ultrasound criteria and aspiration, and laboratory analysis is required. Particle disease and infection cannot be reliably differentiated by ultrasound criteria. In the setting of possible infection, any fluid collection/s around the hip should be treated with suspicion and, if possible, aspirated. The importance of sending part of the aspirated fluid for cell count is stressed; aspirated synovial fluid with a cell count >3000 white blood cells per milliliter of aspirated synovial fluid when combined with an elevated erythrocyte sedimentation rate and C-reactive protein level is highly predictive of infection.
Keywords: postoperative hip; total hip joint replacement; infection; particle disease